2013
DOI: 10.7863/ultra.32.8.1435
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Age‐Related Changes in Left Ventricular Twist by 3‐Dimensional Speckle‐Tracking Echocardiography

Abstract: Three-dimensional speckle-tracking echocardiography can be an effective noninvasive method for assessing 3D LV twist. Age-related differences in the 3D LV twist may be the result of the age-related changes in the endocardial myofibers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 26 publications
0
17
0
1
Order By: Relevance
“…In 2DSTE and 3DSTE studies, there is an agreement that regardless of gender, LV rotational and twist parameters increase with aging. 19,20,22,23 Notomi et al 24 reported that in infancy the LV basal rotation is counterclockwise and it gradually shifts over to clockwise rotation using TDI; in contrast to this finding, Kaku et al 23 found that in infancy the LV basal rotation is clockwise rotation using 3DSTE.…”
Section: Discussionmentioning
confidence: 98%
“…In 2DSTE and 3DSTE studies, there is an agreement that regardless of gender, LV rotational and twist parameters increase with aging. 19,20,22,23 Notomi et al 24 reported that in infancy the LV basal rotation is counterclockwise and it gradually shifts over to clockwise rotation using TDI; in contrast to this finding, Kaku et al 23 found that in infancy the LV basal rotation is clockwise rotation using 3DSTE.…”
Section: Discussionmentioning
confidence: 98%
“…LV untwisting begins in late systole in normal hearts and continues throughout the isovolumic relaxation period, preceding inflow across the mitral valve. LV untwisting is an important mechanism that aids LV filling at a normal LA pressure . Therefore, LV diastolic function depends largely on the degree and rate of LV untwisting.…”
Section: Discussionmentioning
confidence: 99%
“…First, we provided evidence that the 25%Untwist value was a sensi- untwisting is an important mechanism that aids LV filling at a normal LA pressure. 12,13 Therefore, LV diastolic function depends largely on the degree and rate of LV untwisting. Diastolic dysfunction has been attributed to a prolonged untwisting phase and has a significant influence on LV early diastolic filling.…”
Section: %Untwist-a Sensitive Early Diastolic Function Parametermentioning
confidence: 99%
“…In the presented case with calpainopathy, routine echocardiographic examination did not confirm systolic or diastolic heart failure. However, over reduced LV strains, significantly increased LV apical rotation and LV twist were found indicating asymptomatic subclinical (latent) LV dysfunction (26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%